THE PARADIGM OF NEOLOGISM AND ITS IMPACT ON FICTIONAL NARRATIVES - Rustamova Shakhnoza Abdurakhimovna (TADQIQOTLAR.UZ, 2024)
Abstract: This study delves into the impact of neologism on fictional narratives, elucidating its contribution to literary discourse. Employing an interdisciplinary approach, it scrutinizes the manner in which the incorporation of novel lexical entities enhances storytelling, modifies narrative frameworks, and mirrors societal dynamics. Drawing from the fields of literary theory, linguistics, and cultural studies, the research employs a qualitative methodology to scrutinize prominent instances of neologisms within fictional works and their broader implications. Through this analysis, the study aims to unveil the multifaceted roles neologisms play in shaping narratives, offering insights into their linguistic, narrative, and socio-cultural significance.